Optimal Showroom Service Strategy and Power Structure for Retailers considering Consumer Return - Xuemei Zhang; Haoran Chen; Jiawei Hu; Chenhao Ma; Wei Shi (Discrete Dynamics in Nature and Society)
This paper investigates the optimal showroom service strategy and power structure for online and offline retailers considering online consumer return. Combining two service strategies and three competition power structures, six models are constructed to analyze the effects of the showrooming effect and consumer return on retailers’ decisions and consumer surplus. The results show that the SS strategy is the best choice for offline retailers, and it is also an effective way to solve consumer return. Online retailers are suggested to cooperate with offline retailers to implement SS strategy and enhance the showrooming effect. Under the SS strategy, the offline-led power structure is the best choice for online retailers, but the online-led power structure is optimal for offline retailers. We also find that the supply chain and consumers are more likely to implement SS strategy and offline-led power structure. More importantly, we pinpoint that there is no incentive for retailers to implement the Nash power structure. Therefore, it is recommended to revitalize the real economy of offline retailers and implement the strategy SS effectively.